Selectively Defect‐Healed Graphene Electrodes for Tungsten Diselenide Thin‐Film Transistors. (23rd September 2021) - Kim, Tae In; Park, Ick‐Joon
Abstract: 2D nanomaterials such as graphene and transition metal dichalcogenides have attracted great interest as future electronic materials, especially for application in next‐generation displays, owing to their extraordinary electrical, mechanical, and optical properties. In order to achieve 2D material‐based practical devices, it is essential to heal the graphene defects which are inevitably generated during chemical vapor deposition‐based large‐area synthesis and transfer process, through doping technology. In this article, a novel approach for selective defect‐healing of graphene with electrodeposited gold nanoparticles is proposed, where the defect‐healed graphene source/drain electrodes are integrated with p‐type tungsten diselenide (WSe2 ) thin‐film transistors (TFTs), for the first time. This proposed device shows greatly enhanced electrical characteristics (increase of carrier mobility about ≈230.8%) by selective defect‐healing of graphene, and the performance improvement mechanism is systematically investigated in terms of conductivity and Schottky barrier engineering of graphene/WSe2 interface. Also, a long‐term stability of defect‐healed graphene electrode is achieved over a long period of a month, which is enabled by a polymer‐based passivation layer that maintains the doping effects of defect‐engineered graphene. The authors' findings therefore provide a new strategy for developing graphene electrode‐based high‐performance TFTs, and reveal the enormous potential of graphene as an innovative conductor for prospective displays. Abstract : A novel approach for selective defect‐healing of graphene electrode with gold nanoparticles for implementing high‐performance p‐type tungsten diselenide (WSe2 ) thin‐film transistors is proposed. The performance enhancement mechanism of device with defect‐healed graphene is systematically analyzed, revealing the synergetic effect of enhanced conductivity and reduced Schottky barrier between WSe2 and graphene; thus, great potentials of graphene for nanoelectronic devices are demonstrated.